Modern problems of the dagestan languages preservation through the eyes of experts - Yusup Dzh. Dzhabrailov (Кавказология, 2023)
The article handles the problem of studying regional Dagestan languages against the backdrop of an intensive process of urbanization in the republic. Based on an expert survey, modern events in the language sphere and the measures for the development of the Dagestan languages are identified, which affect legislative initiatives at the federal level and the state of native languages in the government. The author pays special attention to the connection between the ethno-cultural education of the younger generation and the formation of manifestations of civic consciousness and patriotic feelings of an individual personality.Thus, the author attempted to analyze the social aspect of the functioning of regional languages. The main purpose of the study is to identify the real picture of the language needs of Dagestan people and to prevent possible social conflicts based on dissatisfaction with the ethno-cultural needs of the population. The author focuses on turning national policy into an effective mechanism for strengthening civic identity, maintaining social stability at the federal, regional levels.